A high molecular weight polyethylene glycol oxalate and a method for its preparation

CN122958480APending Publication Date: 2026-10-23DALIAN UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611064181.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]针对现有聚草酸乙二醇酯(PEOx)熔融缩聚过程中易发生分子内回咬酯交换反应、生成大量环状低聚物,从而导致聚合产率下降、分子量受限及树脂黄变加重等问题,本发明提供一种高分子量聚草酸乙二醇酯及其制备方法,通过大位阻配位钛催化剂的催化作用,保证草酸二酯与乙二醇之间分子间酯交换缩聚反应正常进行的同时,提高高分子链分子内回咬反应的空间位阻,从而降低聚草酸乙二醇酯熔融缩聚过程中环状低聚物生成量,减弱高温缩聚过程中副反应导致的树脂黄变;提高聚草酸乙二醇酯聚合产率、改善树脂色泽

Benefits of technology

(1)本发明通过芳香酚类配体对钛催化中心进行大位阻配位修饰,在催化活性中心周围形成空间屏蔽效应,从而有效抑制聚草酸乙二醇酯熔融缩聚过程中分子内回咬成环反应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application belongs to the technical field of polymer materials, and aims at the problem that polyethylene glycol oxalate is easily catalyzed to pyrolysis into ring, resulting in low molecular weight and yellowing, and discloses a high molecular weight polyethylene glycol oxalate and a preparation method thereof. By constructing a steric hindrance structure around the titanium catalytic active center with aromatic phenolic ligands, the ester exchange polycondensation reaction of oxalic diester, ethylene glycol and oligomers can be normally carried out, the intramolecular backbite conformation formed by the folding of the molecular chain of polyethylene glycol oxalate is difficult to enter the catalytic active area due to the large steric hindrance, thereby realizing the selective inhibition of the intramolecular backbite ring reaction and reducing the generation amount of cyclic oligomers; meanwhile, a branching agent is introduced to further increase the difficulty of the folding backbite of the chain segment to form a ring structure; and the melting polycondensation process is used to realize the inhibition of the generation of cyclic monomers from the three dimensions of catalyst structure, chain structure and process conditions, thereby improving the melting polycondensation yield and molecular weight of polyethylene glycol oxalate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to a high molecular weight poly(ethylene oxalate) (PEOx) and its preparation method. Background Technology

[0002] Polyethylene oxalate (PEOx) is a novel aliphatic polyester material whose main chain contains an oxalate ester structure. Due to the strong electron-withdrawing effect of adjacent dicarbonyl groups in the oxalate structure, the ester bonds of PEOx exhibit high reactivity, thus giving this type of material good biodegradability and chemical recycling potential. Currently, research on PEOx mainly focuses on the preparation of cyclic oxalate monomers and ring-opening polymerization routes. Existing technologies typically involve melt polycondensation of oxalate diesters with aliphatic diols to prepare oligomers, followed by high-temperature depolymerization under reduced pressure to prepare cyclic oxalate monomers, and finally ring-opening polymerization to obtain high molecular weight polyoxalate. For example, CN119350607A discloses a method for preparing polyoxalate from oxalate diesters and aliphatic diols via melt polycondensation, depolymerization to form rings, and ring-opening polymerization; CN119285600A promotes the formation of cyclic monomers by adjusting the copolymer structure. In addition, CN121609890A and CN121607105A also involve related technical routes for the generation of cyclic monomers and continuous polymerization control under high temperature and reduced pressure conditions.

[0003] The aforementioned prior art indicates that polyoxalate readily undergoes intramolecular back-biting transesterification during melt polycondensation, generating cyclic oligomers. Current techniques for preparing polyoxalate utilize this intramolecular back-biting ring-forming characteristic. However, for the direct melt polycondensation of polyethylene oxalate to prepare high-molecular-weight resins, the excessive formation of cyclic oligomers significantly reduces polymerization yield and limits molecular weight increases. Adding subsequent depolymerization, purification, and repolymerization steps would complicate the process and increase costs. On the other hand, existing melt polycondensation systems widely employ small-molecule, highly active titanium-based catalysts such as tetrabutyl titanate. While these catalysts can promote intermolecular transesterification polycondensation, their strong catalytic activity and low steric hindrance also readily catalyze intramolecular back-biting ring-forming reactions in polyethylene oxalate polymer chains, leading to an increase in cyclic oligomers and further inducing thermal degradation, oxidative yellowing, and increased side reactions. Therefore, there is an urgent need to develop a melt polycondensation method that can effectively inhibit intramolecular cyclization reaction of polyoxoethylene glycol ester, reduce the amount of cyclic oligomers generated, and improve the polymer molecular weight and resin color while ensuring the normal intermolecular ester exchange polycondensation. Summary of the Invention

[0004] To address the problems of intramolecular backbiting transesterification reactions and the generation of a large number of cyclic oligomers during the melt polycondensation of poly(ethylene oxalate) (PEOx), which lead to decreased polymerization yield, limited molecular weight, and increased resin yellowing, this invention provides a high molecular weight poly(ethylene oxalate) and its preparation method. Through the catalytic action of a sterically hindered titanium catalyst, the intermolecular transesterification polycondensation reaction between oxalate diester and ethylene glycol proceeds normally while simultaneously increasing the steric hindrance of the intramolecular backbiting reaction in the polymer chain. This reduces the amount of cyclic oligomers generated during the melt polycondensation of PEOx, weakens the resin yellowing caused by side reactions during high-temperature polycondensation, improves the polymerization yield of PEOx, and enhances the resin color.

[0005] In a first aspect, the present invention discloses a method for preparing high molecular weight poly(oxalic acid) glycol ester, comprising the following steps: Oxalate diester and ethylene glycol are added to a reactor in a predetermined ratio, followed by a sterically hindered titanium-based catalyst and a branching agent. Esterification is carried out at 130-180℃ for 6-10 hours, and then the temperature is increased to 180-210℃ for melt polycondensation for 6-12 hours. This process promotes intermolecular transesterification polycondensation while increasing the steric hindrance of intramolecular transesterification reactions, thereby inhibiting the formation of cyclic oligomers.

[0006] Furthermore, the feeding ratio of oxalate diester and ethylene glycol is 1:1.0~1.5.

[0007] Furthermore, the melt polycondensation process adopts a stepwise gradient decompression method, which is divided into an early prepolymerization stage with a vacuum degree >10 kPa and a later final polycondensation stage with a vacuum degree of 10~500 Pa, preferably 20~200 Pa.

[0008] Furthermore, the amounts of the catalyst and branching agent added are calculated based on the total mass of oxalate diester and ethylene glycol. The sterically hindered coordination titanium catalyst of this invention is prepared by coordination exchange between titanate ester compounds and aromatic phenolic ligands under an inert atmosphere.

[0009] Furthermore, the sterically hindered coordinated titanium catalyst is prepared using the following method: Under inert gas protection, a titanium-based catalyst is prepared by adding anhydrous ethanol, isopropanol, or ethylene glycol to form a catalyst solution; then a sterically hindered ligand is added, and the mixture is stirred at 40-80°C for 0.5-4 hours to allow the ligand groups in the sterically hindered ligand to coordinate with the titanium center, thus obtaining a sterically hindered coordinated titanium catalyst.

[0010] Furthermore, the titanium-based catalyst is a titanate compound selected from at least one of tetraisopropyl titanate, tetrabutyl titanate, and tetraethyl titanate. Furthermore, the sterically hindered ligand is an aromatic phenolic ligand selected from at least one of 2,6-di-tert-butylphenol, p-tert-butylphenol, bisphenol A, 2-tert-butylhydroquinone, and 3,5-di-tert-butylsalicylic acid.

[0011] Furthermore, the coordinating group is a hydroxyl, carboxyl, or carbonyl group.

[0012] Furthermore, the molar ratio of the sterically hindered ligand to the titanium element in the titanium-based catalyst is 0.05:1 to 5:1, preferably 0.1 to 2:1.

[0013] The prepared sterically hindered coordination titanium catalyst can be directly used in the transesterification and melt polycondensation reactions of dimethyl oxalate and ethylene glycol. Due to the steric shielding effect of the sterically hindered ligands, some active sites are selectively passivated, thereby reducing the probability of side reactions in the later stages of polycondensation, inhibiting the formation of cyclic oligomers, and improving the polymer molecular weight and product stability.

[0014] Furthermore, the oxalate diester is selected from at least one of dimethyl oxalate, diethyl oxalate, and combinations thereof.

[0015] Furthermore, the amount of the sterically hindered coordination titanium catalyst added is 0.005 to 0.1 wt% of the total mass of oxalate diester and ethylene glycol, preferably 0.01 to 0.05 wt%, and more preferably 0.015 to 0.03 wt%.

[0016] Furthermore, the branching agent is selected from at least one of trimethylolpropane, pentaerythritol, trimellitic anhydride, and citric acid.

[0017] Further, the amount of branching agent added is 0.001-0.1 wt% of the total mass of oxalate and ethylene glycol, preferably 0.005-0.05 wt%, and more preferably 0.01-0.03 wt%. The branching agent reduces the probability of chain segment folding to form intramolecular biting conformations by slightly disrupting the regular conformation of the poly(ethylene oxalate) molecular chain, thereby reducing the amount of cyclic oligomers formed.

[0018] Beneficial effects (1) The present invention modifies the titanium catalytic center with a large steric hindrance by using aromatic phenolic ligands to form a spatial shielding effect around the catalytic active center, thereby effectively inhibiting the intramolecular biting cyclization reaction during the melt polycondensation of polyoxoethylene glycol ester.

[0019] (2) By introducing a small amount of branching agent, the present invention slightly disrupts the regularity of the polyoxoethylene glycol chain structure, increases the difficulty of chain segment folding to form intramolecular back-biting conformation, and further reduces the amount of cyclic oligomers generated from the chain structure level.

[0020] (3) By reducing the probability of intramolecular backbiting and high-temperature side reactions during the melt polycondensation of polyoxoethylene glycol ester, the present invention can effectively reduce the amount of CO, CO2 and colored by-products generated and improve the color of the resin.

[0021] (4) The present invention combines transesterification and melt polycondensation processes, which can improve the polymerization yield and molecular weight of polyoxoethylene glycol ester, and realize the direct melt polycondensation preparation of high molecular weight polyoxoethylene glycol ester resin, thereby reducing process complexity and production costs. Detailed Implementation

[0022] To better understand the above-mentioned objectives, features, and advantages of the present invention, the solutions of the present invention will be further described below. It should be noted that, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other.

[0023] Many specific details are set forth in the following description in order to provide a full understanding of the invention, but the invention may also be practiced in other ways different from those described herein; obviously, the embodiments in the specification are only some embodiments of the invention, and not all embodiments.

[0024] The preferred embodiments of the present invention will now be described in detail with reference to specific examples. It should be understood that the following examples are given for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications and substitutions to the present invention without departing from its spirit and essence.

[0025] Test instrument model: In the embodiments and comparative examples of this invention, the number-average molecular weight (Mn) of the polymer was tested by gel permeation chromatography (GPC) using a Waters 1515 gel permeation chromatograph with hexafluoroisopropanol as the mobile phase and polystyrene standard sample as the calibration.

[0026] The content of cyclic oligomers in the polymer and the content of cyclic monomers in the polycondensation distillate were determined by Agilent 7890B gas chromatography (GC). The yellowness (b value) of the resin was tested using a Konica Minolta CM-3600A colorimeter.

[0027] Example 1: First, a sterically hindered coordination passivated titanium-based catalyst was prepared: Under nitrogen protection, tetraisopropoxy titanium and 2,6-di-tert-butylphenol were added to anhydrous ethanol at a molar ratio of 1:2, and the mixture was stirred at 80°C for 2 hours to allow the aromatic phenolic ligands to coordinate with the titanium center. Subsequently, some solvent was removed under reduced pressure to obtain a sterically hindered coordination titanium-based catalyst solution for later use. Then, dimethyl oxalate and ethylene glycol were added at a molar ratio of 1:1.25 to a reactor equipped with mechanical stirring, temperature control, and a vacuum system. 0.02 wt% of the above-mentioned sterically hindered coordination titanium-based catalyst was added based on the total mass of dimethyl oxalate and ethylene glycol. The transesterification reaction was carried out at 165°C and atmospheric pressure for 6 hours, continuously distilling off methanol byproducts. The temperature was then raised to 185°C and gradually reduced to 10 kPa for pre-polymerization for 1 hour to promote oligomer chain growth. Finally, the temperature was further raised to 195°C and the pressure reduced to 50 Pa for final polymerization for 10 hours. After the reaction was completed, the polymer melt was discharged, cooled, pulverized, and then vacuum dried at 60°C for 12 hours to constant weight, yielding a pale yellow polyoxoethylene glycol resin. The obtained polymer had a number-average molecular weight (Mn) of 43,800, a cyclic oligomer content of 3.2%, a cyclic monomer percentage of 10.4% in the polycondensation distillate, a polymerization yield of 75.0%, and a resin b-value of 10.1.

[0028] Example 2: First, a sterically hindered coordination titanium catalyst was prepared according to the method in Example 1, except that bisphenol A was used as the aromatic phenolic ligand, and the molar ratio of tetrabutyl titanate to bisphenol A was controlled at 1:1. The reaction was stirred at 100°C for 2 hours. Then, dimethyl oxalate and ethylene glycol were added to the reaction system at a molar ratio of 1:1.12. 0.022 wt% of the sterically hindered coordination titanium catalyst was added based on the total mass of dimethyl oxalate and ethylene glycol, and 0.02 wt% pentaerythritol was added as a branching structure regulator. The transesterification stage was controlled at 170°C for 8 hours, then gradually reduced to 12 kPa and continued at 188°C for 2 hours. Finally, final polycondensation was carried out at 198°C and 40 Pa for 9 hours. After polymerization, the product was discharged, cooled, pulverized, and vacuum dried to obtain a light yellow poly(ethylene oxalate) resin. The obtained polymer had a number-average molecular weight (Mn) of 42,100, a cyclic oligomer content of 3.6%, a cyclic monomer content of 11.2% in the polycondensation distillate, a polymerization yield of 72.8%, and a resin b-value of 11.8.

[0029] Example 3: First, under nitrogen protection, tetraethyl titanate and p-tert-butylphenol were added to anhydrous ethanol at a molar ratio of 1:2 and reacted at 85°C for 2 hours to prepare a sterically hindered titanium catalyst with alkyl-substituted phenol coordination modification. Then, diethyl oxalate and ethylene glycol were added to a reactor at a molar ratio of 1:1.10. 0.028 wt% of the above-mentioned coordinated titanium catalyst was added based on the total mass of diethyl oxalate and ethylene glycol, and 0.018 wt% citric acid was added as a branching structure regulator. First, a transesterification reaction was carried out at 168°C and atmospheric pressure for 10 hours, followed by pre-polymerization at 182°C and reduced pressure to 15 kPa for 2 hours, and finally final polymerization at 190°C and 60 Pa for 8 hours. After the reaction, the product was cooled, pulverized, and vacuum dried to obtain poly(ethylene oxalate) resin. The obtained polymer had a number-average molecular weight (Mn) of 44,700, a cyclic oligomer content of 3.4%, a cyclic monomer content of 10.8% in the polycondensation distillate, a polymerization yield of 74.1%, and a resin b-value of 11.4.

[0030] Example 4: First, a sterically hindered coordination titanium catalyst was prepared by coordinating 2,6-di-tert-butylphenol with tetraisopropoxy titanium, using the same method as in Example 1. Then, dimethyl oxalate and ethylene glycol were added to the reaction system at a molar ratio of 1:1.18. 0.026 wt% of the sterically hindered coordination titanium catalyst was added based on the total mass of dimethyl oxalate and ethylene glycol, along with 0.030 wt% trimethylolpropane as a branching structure regulator. The reaction was first carried out at 165°C under normal pressure for 8 hours, followed by a pre-polymerization reaction at 186°C and gradually reduced to 20 kPa for 2 hours. Finally, a final polymerization was carried out at 200°C and 30 Pa for 8 hours. After polymerization, the polymer melt was discharged, cooled, pulverized, and vacuum dried to obtain a pale yellow poly(ethylene oxalate) resin. The obtained polymer had a number-average molecular weight of 45,100, a cyclic oligomer content of 3.3%, a cyclic monomer content of 10.1% in the polycondensation distillate, a polymerization yield of 74.6%, and a resin b-value of 10.2.

[0031] Comparative Example 1: Uncoordinated tetrabutyl titanate was used as the catalyst, and no branching modifier was added. All other process conditions were the same as in Example 1. The resulting polymer had a number-average molecular weight (Mn) of 38,700, a cyclic oligomer content of 7.9%, a cyclic monomer percentage of 18.6% in the polycondensation distillate, a polymerization yield of 63.5%, and a resin b-value of 12.4.

[0032] Comparative Example 2: A tetrabutyl titanate catalytic system without coordination modification was used, and the catalyst addition was increased to 0.08 wt%, with other conditions the same as in Example 1. The resulting polymer had a number-average molecular weight (Mn) of 40,200, a cyclic oligomer content of 9.3%, a cyclic monomer content of 21.5% in the polycondensation distillate, a polymerization yield of 60.8%, and a resin b-value of 14.1.

[0033] Comparative Example 3: A sterically hindered titanium-based catalytic system was used, but no branching structure modifier was added; all other conditions were the same as in Example 1. The resulting polymer had a number-average molecular weight of 41,500, a cyclic oligomer content of 5.6%, a cyclic monomer content of 14.3% in the polycondensation distillate, a polymerization yield of 68.9%, and a resin b-value of 10.9.

[0034] Comparative Example 4: A one-step high-temperature, high-vacuum melt polycondensation process was employed, with continuous polycondensation at 210°C and 50 Pa for 8 hours, while other conditions remained the same as in Example 1. The resulting polymer had a number-average molecular weight (Mn) of 39,800, a cyclic oligomer content of 8.5%, a cyclic monomer percentage of 19.4% in the polycondensation distillate, a polymerization yield of 61.7%, and a resin b-value of 13.2.

[0035] Table 1. Summary of Performance Data for Examples and Comparative Examples Test Result Analysis As shown in Table 1, the sterically hindered coordination titanium catalytic systems modified with aromatic phenolic ligands in Examples 1-4 of this invention, combined with a small amount of branching structure modifier, all produced polyoxoethylene glycol esters with high molecular weight (Mn of 42100-45100), low cyclic oligomer content (3.2%-3.6%), and polymerization yields of 72.8%-75.0%, while the resin yellow index remained at a low level.

[0036] Compared to Comparative Examples 1 and 2, which used uncoordinated tetrabutyl titanate, the embodiments of the present invention significantly reduced the amount of cyclic byproducts and increased the polymerization yield and molecular weight, indicating that the sterically hindered coordination structure can effectively inhibit the intramolecular biting cyclization reaction during the melt polycondensation of poly(ethylene oxalate). Comparative Example 3 showed that the branching structure regulator could further reduce the content of cyclic oligomers; Comparative Example 4 showed that the segmented heating, gradient decompression, and dynamic removal of small molecules were beneficial in reducing side reactions and improving polymerization efficiency. Therefore, the present invention achieves the efficient preparation of high molecular weight poly(ethylene oxalate) through the synergistic effect of the catalytic system, chain structure regulation, and polymerization process.

Claims

1. A sterically hindered coordination titanium catalyst, characterized in that, It was prepared using the following method: Under inert gas protection, a titanium-based catalyst is added to an anhydrous solvent to prepare a catalyst solution; then a sterically hindered ligand is added, and the mixture is stirred at 40~80℃ for 0.5~4h to allow the ligand groups in the sterically hindered ligand to coordinate with the titanium center, thus obtaining a sterically hindered coordinated titanium catalyst. The titanium-based catalyst is a titanate compound selected from at least one of tetrapropyl titanate, tetrabutyl titanate, and tetraethyl titanate. The sterically hindered ligand is an aromatic phenolic ligand selected from at least one of 2,6-di-tert-butylphenol, p-tert-butylphenol, bisphenol A, 2-tert-butylhydroquinone, and 3,5-di-tert-butylsalicylic acid. The anhydrous solvent is selected from anhydrous ethanol, isopropanol, or ethylene glycol.

2. The sterically hindered coordination titanium catalyst according to claim 1, characterized in that, The molar ratio of the sterically hindered ligand to titanium in the titanium-based catalyst is 0.05 to 5:

1.

3. The sterically hindered coordination titanium catalyst according to claim 2, characterized in that, The molar ratio of the sterically hindered ligand to titanium in the titanium-based catalyst is 0.1~2:

1.

4. A method for preparing high molecular weight poly(oxalic acid) glycol ester, characterized in that, Includes the following steps: Oxalate and ethylene glycol are added to a reaction vessel in a predetermined ratio, and then a sterically hindered titanium-based catalyst and a branching agent are added. Esterification is carried out at 130-180℃ for 6-10 hours, and then the temperature is increased to 180-210℃ for melt polycondensation reaction for 6-12 hours to obtain high molecular weight polyoxoethylene glycol ester.

5. The method for preparing high molecular weight polyoxoethylene glycol ester according to claim 4, characterized in that, The branching agent is selected from at least one of trimethylolpropane, pentaerythritol, trimellitic anhydride, and citric acid.

6. The method for preparing high molecular weight polyoxoethylene glycol ester according to claim 4, characterized in that, The amount of branching agent added is 0.001 to 0.1 wt% of the total mass of oxalate and ethylene glycol.

7. The method for preparing high molecular weight polyoxoethylene glycol ester according to claim 4, characterized in that, The amount of the sterically hindered coordination titanium catalyst added is 0.005 to 0.1 wt% of the total mass of oxalate diester and ethylene glycol.

8. The method for preparing high molecular weight polyoxoethylene glycol ester according to claim 4, characterized in that, The ratio of oxalate diester to ethylene glycol is 1:1.0~1.5; the oxalate diester is selected from at least one of dimethyl oxalate and diethyl oxalate.

9. The method for preparing high molecular weight polyoxoethylene glycol ester according to claim 4, characterized in that, The melt polycondensation process adopts a stepwise gradient decompression method, with the absolute pressure in the prepolymerization stage being >10 kPa and the absolute pressure in the final polycondensation stage being 10~500 Pa.

10. A high molecular weight polyoxoethylene glycol ester, characterized in that, It is prepared by the preparation method described in any one of claims 4-9.

Citation Information

Patent Citations

  • Preparation method of cyclic alkyl oxalate and ring-opening copolymerization of cyclic alkyl oxalate

    CN119285600A

  • Preparation method of high molecular weight poly (alkyl oxalate) homopolymer and copolymer

    CN119350607A

  • Device and method for continuous production of poly (p-dioxanone)

    CN121607105A

  • Method for continuously producing poly (p-dioxanone)

    CN121609890A